Systematic reviews in mobile app software engineering: A tertiary study - Zein, Samer; Salleh, Norsaremah; Grundy, John (Elsevier, 2023)
Context: A number of secondary studies in the form of systematic reviews and systematic mapping studies exist in the area of mobile application software engineering. Objective: The focus of this paper is to provide an overview and analysis of these secondary studies of mobile app software engineering for researchers and practitioners. Method: We conducted a systematic tertiary study following the guidelines by Kitchenham et al. to classify and analyze secondary studies in this area. Results: After going through several filtration steps, we identified 24 secondary studies addressing major software engineering phases, such as initiation, requirements engineering, design, development and testing. The majority of the secondary studies focused on testing and design phases. Specific research topics addressed by the included studies were: usability evaluation, test automation, context-aware testing, cloud-based development, architectural models, effort and size estimation models, defect prediction, and GUI testing. We found that the trend in secondary studies is towards more specific areas of mobile application software engineering such as architectural design models, context-aware testing, testing of non-functional requirements, mobile cloud computing, and intelligent mobile applications. Research directions and some identified practices for practitioners were also identified. Conclusions: Mobile application software engineering is an active research area. The area can benefit from additional research in terms of secondary studies targeting evolution, maintenance, requirements engineering, and cross-platform mobile application development. Additionally, some of the secondary studies identify some useful practices for practitioners.